The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0104-66322011000300016
|View full text |Cite
|
Sign up to set email alerts
|

3D-CFD simulation and neural network model for the j and f factors of the wavy fin-and-flat tube heat exchangers

Abstract: A three dimensional (3D) computational fluid dynamics (CFD) simulation and a neural network model are presented to estimate the behaviors of the Colburn factor (j) and the Fanning friction factor (f) for wavy fin - and - flat tube (WFFT) heat exchangers. Effects of the five geometrical factors of fin pitch, fin height, fin length, fin thickness, and wavy amplitude are investigated over a wide range of Reynolds number (600 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…According to our previous studies [31][32][33], enhancement of flow path and generation of swirl flows along/perpendicular to the flow direction are the remarkable phenomena in the wavy channels. It seems that the geometry of the cross-section can considerably affect the number, strength, and location of these swirl flows inside the WMC.…”
Section: Effect Of Cross-section Geometry On Performance Of Wmcmentioning
confidence: 91%
“…According to our previous studies [31][32][33], enhancement of flow path and generation of swirl flows along/perpendicular to the flow direction are the remarkable phenomena in the wavy channels. It seems that the geometry of the cross-section can considerably affect the number, strength, and location of these swirl flows inside the WMC.…”
Section: Effect Of Cross-section Geometry On Performance Of Wmcmentioning
confidence: 91%
“…Some researchers have studied the effects of some of the aforementioned parameters on the thermal-hydraulic performance of flat tube HE. Numerous numerical and experimental studies have been done to determine the air-side thermal and flow performances using different types of tubes and fins [10,[18][19][20][21][22]. Nascimento and Garcia [23] reported that flat tube with a shallow square dimple enhanced the heat transfer considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Wavy fin was another type of fin. Khoshvaght et al [9] established the mathematical model of the wavy fin-and-flat-tube heat exchanger to analyze the heat transfer and resistance performance. Of course, there were improvements around fins in recent years.…”
Section: Introductionmentioning
confidence: 99%